2019
DOI: 10.1002/chem.201805148
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Metal Oxido Compounds with B(C6F5)3

Abstract: Lewis acid-base pair chemistry has been placed on an ew level with the discovery that adduct formationb etween an electron donor (Lewis base) and acceptor (Lewis acid) can be inhibited by the introductiono fs teric demand, thus preserving the reactivityo fb oth Lewis centers, resulting in highly unusual chemistry.S ome of these highly versatile frustrated Lewis pairs (FLP) are capable of splitting avariety of small molecules, such as dihydrogen, in ah eterolytic and even catalytic manner.T his is in sharp cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 160 publications
1
13
0
Order By: Relevance
“…Notably,a fter heating 3 at 393 Kfor 30 min about 30 %ofclean conversiont o2 was measured by 31 P{ 1 H} NMR spectroscopy,t hus indicating that 2 is a system capable of affording reversible uptake and releaseo f H 2 . [8,9] Complex 2 also activates the polar OÀHb ond of water.N otably,a ddition of excess of water to THF solutionso fc omplex 2 does not produce significant changes in its 1 Ha nd 31 PNMR spectra.H owever,N MR and MS measurements clearly indicate that complex 2 reacts with deuterated water in ar eversible fashion resulting in the deuteration of the Cp* group. The 31 P{ 1 H} NMR spectrum of [D 8 ]THF/D 2 O( 78 %/22 %, v/v) solutions does not change over time but the 1 HNMR spectrumw as found to be time-dependent.…”
mentioning
confidence: 99%
“…Notably,a fter heating 3 at 393 Kfor 30 min about 30 %ofclean conversiont o2 was measured by 31 P{ 1 H} NMR spectroscopy,t hus indicating that 2 is a system capable of affording reversible uptake and releaseo f H 2 . [8,9] Complex 2 also activates the polar OÀHb ond of water.N otably,a ddition of excess of water to THF solutionso fc omplex 2 does not produce significant changes in its 1 Ha nd 31 PNMR spectra.H owever,N MR and MS measurements clearly indicate that complex 2 reacts with deuterated water in ar eversible fashion resulting in the deuteration of the Cp* group. The 31 P{ 1 H} NMR spectrum of [D 8 ]THF/D 2 O( 78 %/22 %, v/v) solutions does not change over time but the 1 HNMR spectrumw as found to be time-dependent.…”
mentioning
confidence: 99%
“…Our previously described molybdenum oxido imido adducts [Mo{OB(C 6 F 5 ) 3 }(N t Bu)L 2 ] were found to catalyze the hydrosilylation of benzaldehyde [23,26] . We demonstrated that benzaldehyde inserts into the B−H bond during catalysis.…”
Section: Resultsmentioning
confidence: 78%
“…Our previously described molybdenum oxido imido adducts [Mo{OB(C 6 F 5 ) 3 }(N t Bu)L 2 ] were found to catalyze the hydrosilylation of benzaldehyde. [ 23 , 26 ] We demonstrated that benzaldehyde inserts into the B−H bond during catalysis. Similar observations were made recently in the hydrosilylation of carbonyl compounds catalyzed by hydridoborenium borate salts, where also insertion into the B−H bond was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We commenced our investigations by checking the stability of N MoN and P MoN with the strong Lewis acid (LA) B(C 6 F 5 ) 3 . Treating solutions thereof in either deuterated benzene or toluene with an equimolar amount of B(C 6 F 5 ) 3 at room temperature immediately led to the quantitative formation of the new compounds N 1 and P 1 according to NMR ( 1 H, 11 B, 19 F and 31 P) analysis (Scheme 1). For both Mo compounds, the boron resonance of B(C 6 F 5 ) 3 in the 11 B NMR spectra was strongly shifted to higher fields, from 58 to 4 and À 5 ppm when complexed to N MoN and P MoN, respectively.…”
Section: Resultsmentioning
confidence: 99%